The prospects of e-Commerce in Ukraine - Lysak, H. (Мелітополь: ТДАТУ, 2018)
The integration of local networks into the global Internet network and the development of information technologies have led to a significant increase in the speed of information exchange. As the worldwide network became popular and spread out, it became an integral part of the business. At initial period of Internet use the entrepreneurs were limited to electronic correspondence. Today it is difficult to imagine a successful company not using the Internet for business. Any company needs information support of its business processes, as well as information interaction on-line with the external environment - branches in other cities and countries, customers, suppliers. The role played by the Internet for business and Commerce is much wider, than just communication. It includes making deals, advertising, making purchases, making payments, receiving feedback and, as a result, increasing the volume of the market for a particular company.
Keywords: e-Commerce; integration